Improved Efficiency of All-Inorganic Quantum-Dot Light-Emitting Diodes via Interface Engineering - Xu, Qiulei; Li, Xinyu; Lin, Qingli; Shen, Huaibin; Wang, Hongzhe; Du, Zuliang (Frontiers in Chemistry, 2020)
As the charge transport layer of quantum dot (QD) light-emitting diodes (QLEDs), metal oxides are expected to be more stable compared with organic materials. However, the efficiency of metal oxide-based all-inorganic QLEDs is still far behind that of organic–inorganic hybrid ones. The main reason is the strong interaction between metal oxide and QDs leading to the emission quenching of QDs. Here, we demonstrated nickel oxide (NiOx)-based all-inorganic QLEDs with a maximum current efficiency of 20.4 cd A−1 and external quantum efficiency (EQE) of 5.5%, which is among the most efficient all-inorganic QLEDs. The high efficiency is mainly attributed to the aluminum oxide (Al2O3) deposited at the NiOx/QDs interface to suppress the strong quenching effect of NiOx on the QD emission, together with the molybdenum oxide (MoOx) that reduced the leakage current and facilitated hole injection, more than 300% enhancement was achieved compared with the pristine NiOx-based QLEDs. Our study confirmed the effect of decorating the NiOx/QDs interface on the performance enhancement of the all-inorganic QLEDs.